The role of Tyr(605) and Ala(607) of thimet oligopeptidase and Tyr(606) and Gly(608) of neurolysin in substrate hydrolysis and inhibitor binding - Machado, Mauricio F. M. [UNIFESP] (2007)
The physicochemical properties of TOP (thimet oligopeptidase) and NEL (neurolysin) and their hydrolytic activities towards the FRET (fluorescence resonance energy transfer) peptide series AbzGFSXFRQ-EDDnp [where Abz is o-aminobenzoyl; X = Ala, Ile, Leu, Phe, Tyr, Trp, Ser, Gln, Glu, His, Arg or Pro; and EDDnp is N-(2,4-dinitrophenyl)-ethylenediamine] were compared with those of site-mutated analogues. Mutations at Tyr(605) and Ala(607) in TOP and at Tyr(606) and Gly(608) in NEL did not affect the overall folding of the two peptidases, as indicated by their thermal stability, CD analysis and the pH-dependence of the intrinsic fluorescence of the protein. the kinetic parameters for the hydrolysis of substrates with systematic variations at position P-1 showed that Tyr(605) and Tyr(606) of TOP and NEL respectively, played a role in subsite S-1. Ala(607) of TOP and Gly(608) of NEL contributed to the flexibility of the loops formed by residues 600-612 (GHLAGGYDGQYYG; one-letter amino acid codes used) in NEL and 599-611 (GHLAGGYDAQYYG; one-letter amino acid codes used) in TOP contributing to the distinct substrate specificities, particularly with an isoleucine residue at P-1. TOP Y605A was inhibited less efficiently by JA-2 {N-[1-(R,S)-carboxy-3-phenylpropyl]Ala-Aib-Tyr-p-aminobenzoate}, which suggested that the aromatic ring of Ty,105 was an important anchor for its interaction with wild-type TOP. the hydroxy groups of Tyr 605 and Tyr.. did not contribute to the pH-activity profiles, since the pKs obtained in the assays of mutants TOP Y605F and NEL Y606F were similar to those of wild-type peptidases. However, the pH-k(cat)/K-m dependence curve of TOP Y605A differed from that of wild-type TOP and from TOP Y606F. These results provide insights into the residues involved in the substrate specificities of TOP and NEL and how they select cytosolic peptides for hydrolysis.